1996
DOI: 10.1159/000227555
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Vinorelbine in Heavily Previously Treated Small Cell Lung Cancer

Abstract: Twenty-four previously treated patients with refractory or relapsed small cell lung cancer (SCLC) were entered into a prospective, multicenter phase II study. All 24 patients had been pretreated with some form of cisplatin-based chemotherapy. The median time of chemotherapy was 4.2 months (range 1.4–9.4 months). Patients were treated with a dose of 25 mg/m2 of vinorelbine weekly. Twenty-four patients were eligible for response and for toxicity. Partial response was observed in 3 out of 24 eligible p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 9 publications
0
17
0
2
Order By: Relevance
“…A randomized phase III trial comparing topotecan chemotherapy to best supportive care demonstrated signifi cant prolongation Several reports have been made on single-agent activity for newer chemotherapeutic agents, including irinotecan, [20][21][22] topotecan, 23 paclitaxel, 24,25 docetaxel, 26 gemcitabine, 27,28 and vinorelbine, 29,30 in the second-line setting. However, few single agents can elicit a good response in patients with early relapse or disease progression during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized phase III trial comparing topotecan chemotherapy to best supportive care demonstrated signifi cant prolongation Several reports have been made on single-agent activity for newer chemotherapeutic agents, including irinotecan, [20][21][22] topotecan, 23 paclitaxel, 24,25 docetaxel, 26 gemcitabine, 27,28 and vinorelbine, 29,30 in the second-line setting. However, few single agents can elicit a good response in patients with early relapse or disease progression during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple other chemotherapies have shown activity comparable to topotecan in the second-line setting, including irinotecan (50), paclitaxel (51,52), docetaxel (53), gemcitabine (54,55), vinorelbine (56,57), and temozolomide (58,59). Regardless of the cytotoxic regimen used, patients with "sensitive" disease (relapse >90 days after completion of first line therapy) overall have better outcomes than patients with "refractory" disease.…”
Section: Extensive Stage Sclc: Systemic Therapymentioning
confidence: 99%
“…Several other cytotoxic agents, including taxanes, gemcitabine, vinorelbine, irinotecan and pemetrexed, have been investigated as second-line treatment, in either single-agent or combination treatment (table 3) [41,65,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. Some agents, such as paclitaxel and irinotecan, have shown some degree of activity in phase II trials.…”
Section: Second-line Treatment For Es-sclcmentioning
confidence: 99%